A comparison of objective and subjective measurements of non-nutritive sucking in preterm infants - Luh Karunia Wahyuni; Irawan Mangunatmadja; Risma Kerina Kaban; Elvie Zulka Kautzia Rachmawati; Melinda Harini; Budiati Laksmitasari; Agatha Geraldyne; Inez Ayuwibowo Sangwidjojo; Dini Prima Utami; Victor Prasetyo Poernomo; Adrian Prasetya Sudjono (Indonesian Pediatric Society, 2022)
Background Of preterm infants born before 32 weeks of gestation, 40-70% have atypical and immature feeding skills, which could delay initiation of oral feeding. A formal objective measurement of non-nutritive sucking may increase the accuracy of determining the right time to initiate oral feeding, however, most hospital perinatology care units do not own a suction pressure measurement device to objectively measure non-nutritive sucking parameters. Objective To compare objective and subjective non-nutritive sucking (NNS) based on sucking pressure, number of suctions per burst, and time between bursts. Methods One hundred twenty preterm infants born at 28-34 weeks’ gestation were evaluated for objective and subjective NNS. Data were collected from August to November 2021 at five hospitals in Jakarta. Objective NNS was measured by a suction pressure measurement device, while subjective NNS was clinically examined. Number of suctions per burst, sucking pressure, and time between bursts were analysed by Spearman’s correlation test. Results A positive and significant correlation between objective and subjective NNS was found in all parameters (P<0.001). The highest correlation was found in time between bursts (r=0.74; P<0.001), followed by number of suctions per burst (r=0.60; P<0.001), and sucking pressure (r=0.58; P<0.001). Conclusion The correlation between objective and subjective NNS examination was moderate in preterm infants. Therefore, an objective NNS measurement is still required for optimizing the examination.